God without religion - "Saranam, Sankara" (Cochin, 2005)
I've started reading the first 3 chapters and I can tell I'm going to like this book. Atheists, agnostics, and people wondering about their faith, might find this helpful. If you have a lot of questions about God, it seems deep but interesting and understandable. It was written by a man who used to be a monk. Married now, with a couple of degree's. In fact instead of driving me away from religion it brought me closer. In a way it seems we all develop our own religion, any ways. This book is opening my mind more and talking about things organized religion doesn't talk about. So far a good book.
Keywords: Truth